Real-world 2-year treatment patterns among patients with psoriatic arthritis treated with injectable biologic therapies. (2nd July 2020) - Walsh, Jessica A.; Cai, Qian; Lin, Iris; Fitzgerald, Timothy; Pericone, Christopher D.; Chakravarty, Soumya D.
Abstract: Objectives: To assess long-term (2-year) biologic treatment patterns of psoriatic arthritis (PsA) patients who initiated adalimumab, certolizumab pegol, etanercept, golimumab, or ustekinumab. Methods: Adult patients with ≥1 pharmacy or medical claim for injectable PsA biologics (index date) were identified from the Optum's Clinformatics Data Mart (1 January 2013–31 December 2016). Adherence, persistence, post-discontinuation treatment patterns, and addition of adjunctive medications were evaluated by index biologic. Results: Of 996 patients included (mean [SD] age: 51.5 [12.6] years; female: 49.4%), the most common index biologics initiated were adalimumab (47.9%) and etanercept (34.5%). The mean [SD] proportion of days covered was 0.48 [0.32] for the index biologics. During the 24-month follow-up period, 19.7% of patients persisted on their index biologic; ustekinumab had the highest persistence rate (27.2%), followed by adalimumab (22.0%), golimumab (18.4%), certolizumab pegol (15.6%), and etanercept (15.4%). Of the 800 patients (80.3%) who discontinued their index biologic therapy, 35.0% restarted, 40.1% switched to another biologic, and 31.8% did neither during the follow-up period. The most common biologics patients switched to were adalimumab (31.2%) and ustekinumab (18.7%). Among patients who persisted with their index biologic for ≥90 days ( n = 753), ≥1 adjunctive medication was added for 50.1% of patients. The most common adjunctive medications included corticosteroids (28.0% of patients), opioids (17.0%), nonsteroidal anti-inflammatory drugs (NSAIDs) (13.8%), and conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) (7.3%). Conclusions: In this real-world study of use of biologic PsA therapies, 24-month persistence was low (19.7%), and treatment was frequently supplemented with adjunctive medications.